Transient Crossed Aphasia: A Case Study with SPECT - José M. Ferro; Guilhermina Cantinho; Élia Baeta (Behavioural Neurology)
A 45-year-old right-handed man developed “crossed” anomie aphasia, neglect and inaccurate reaching of his left arm in both hemispaces due to a right parietal haemorrhage. Aphasia cleared in a few days. SPECT failed to demonstrate crossed left hemispheric diaschisis. This report emphasizes the importance of evaluating patients in the acute stage and of coupling “static” and “functional” imaging methods when studying brain-behavior relationships.